Global trends and interdisciplinary insights in Tai Chi research: a bibliometric analysis (2004–2024) - Bei Li; Xiwei Zhu; Xiwei Zhu; Xiwei Zhu; Haoli Zhang; Su Zhang; Yanwei Li; Shuxi Wu; Shuxi Wu; Shuxi Wu; Jie Han; Jie Han; et al. (Frontiers in Medicine)
BackgroundTai Chi, as a traditional Chinese martial art, has received extensive attention in recent years due to its multiple health benefits. Research demonstrates that Tai Chi improves physical health, enhances flexibility and coordination, and alleviates psychological stress. With the increase in research, the health benefits of Tai Chi have been confirmed by many scientific studies. Therefore, a bibliometric analysis of Tai Chi literature can help us better understand the research status and development trends in this field.MethodsThe article and commentary on Tai Chi from 2004 to 2024 were retrieved from the Web of Science Core Collection. We used the bibliometric.com online platform and VOSviewer software to analyze the collaboration between countries/institutions/journals/authors, as well as the co-occurrence of keywords and research hotspots. Disciplinary distribution was analyzed using Web of Science subject categories, and visualized through VOSviewer’s clustering algorithm.ResultsFrom 2004 to 2023, the number of research papers related to Tai Chi showed an overall upward trend, with a 12.3% average annual growth rate post-2012. China contributed 68.5% of publications (n = 645/941), followed by the United States (15.2%, n = 143). Key findings include a 40% reduction in fall risk (RR = 0.60, 95% CI: 0.52–0.69) and a 33% improvement in sleep quality (p < 0.001) among elderly practitioners. The author collaboration network map shows that authors like Wayne, Peter M. have significant influence in the field of Tai Chi research. Keyword co-occurrence analysis reveals several main themes in Tai Chi research: health benefits, disease management, psychological and social benefits, and regional and cultural factors.ConclusionTai Chi research is growing globally, and its potential health benefits are increasingly recognized. China leads in Tai Chi research, with growing research in other countries and regions. Tai Chi research is interdisciplinary, involving multiple academic fields. Tai Chi has potential value in improving the health of the elderly, preventing falls, enhancing cognitive function, and managing chronic diseases. Future research can further explore the long-term effects, mechanisms of action, and application in different populations.